2018
DOI: 10.1016/j.biomaterials.2018.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Tumor hypoxia directed multimodal nanotherapy for overcoming drug resistance in renal cell carcinoma and reprogramming macrophages

Abstract: Drug resistance is one of the significant clinical burden in renal cell carcinoma (RCC). The development of drug resistance is attributed to many factors, including impairment of apoptosis, elevation of carbonic anhydrase IX (CA IX, a marker of tumor hypoxia), and infiltration of tumorigenic immune cells. To alleviate the drug resistance, we have used Sorafenib (Sor) in combination with tumor hypoxia directed nanoparticle (NP) loaded with a new class of apoptosis inducer, CFM 4.16 (C4.16), namely CA IX-C4.16. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 67 publications
(103 reference statements)
0
42
0
Order By: Relevance
“…From Figure 4F, it can be seen that the IFN-γ production in PDL1-Dox treatment is significantly higher compared to Dox in a co-cultured condition of MDA-MB-231 and activated RAW 264.7 cells. Literature reports indicate that activation of Raw 264.7 (macrophage) cells with lipopolysaccharide (LPS) can significantly upregulate the PD-1 expression [25,26]. Towards this end, we have utilized the LPS activated Raw 265.7 cells co-cultured with MDA-MB-231 and found the up-modulation of IFN-γ, suggesting the PDL1-Dox mediated inhibition of PD1 and PDL1 interaction.…”
Section: Resultsmentioning
confidence: 87%
“…From Figure 4F, it can be seen that the IFN-γ production in PDL1-Dox treatment is significantly higher compared to Dox in a co-cultured condition of MDA-MB-231 and activated RAW 264.7 cells. Literature reports indicate that activation of Raw 264.7 (macrophage) cells with lipopolysaccharide (LPS) can significantly upregulate the PD-1 expression [25,26]. Towards this end, we have utilized the LPS activated Raw 265.7 cells co-cultured with MDA-MB-231 and found the up-modulation of IFN-γ, suggesting the PDL1-Dox mediated inhibition of PD1 and PDL1 interaction.…”
Section: Resultsmentioning
confidence: 87%
“…This nanoparticle delivery subsequently reprogrammed macrophages to an M1-like state in vitro, via inhibition of AKT1 phosphorylation preventing the activation of STAT6. Nanoparticle-treatment potently inhibited tumour growth in a mouse model of renal cell carcinoma [109]. Similarly, Zhang et al recently reported on the combination of sorafinib with HDAC inhibitor panobinostat and bromodomain protein inhibitor OTX015.…”
Section: Targeting Tumour-associated Macrophages In the Tumour Micmentioning
confidence: 99%
“…In this context, nanocarriers need to provide sufficient therapeutic efficacy, and issues such as unfavorable biodistribution or rapid drug clearance from tumor areas must be resolved [ 81 ]. Furthermore, nanocarriers will experience a prolonged presence in the blood flow, aggregate in the tumor microenvironment, and facilitate efficient drug uptake by cancer cells [ 82 ].…”
Section: Nanotechnology In Pdtmentioning
confidence: 99%